Modeling spatiotemporal impacts of hydroclimatic extremes on groundwater recharge at a Mediterranean karst aquifer - Hartmann, Andreas; Andreo-Navarro, Bartolomé; Marín-Guerrero, Ana Isabel; Wagener, Thorsten; Lange, Jens; Mudarra-Martínez, Matías; Marín-Guerrero, Ana Isabel (American Geophysical Union., 2014)
Karst aquifers provide large parts of the water supply for Mediterranean countries, though climate change is expected to have a significant negative impact on water availability. Recharge is therefore a key variable that has to be known for sustainable groundwater use. In this study, we present a new approach that combines two independent methods for karst recharge estimation. The first method derives spatially distributed information of mean annual recharge patterns through GIS analysis. The second is a process-based karst model that provides spatially lumped but temporally distributed information about recharge. By combining both methods, we add a spatial reference to the lumped simulations of the process-based model. In this way, we are able to provide spatiotemporal information of recharge and subsurface flow dynamics also during varying hydroclimatic conditions. We find that there is a nonlinear relationship between precipitation and recharge rates resulting in strong decreases of recharge following even moderate decreases of precipitation. This is primarily due to almost constant actual evapotranspiration amounts despite varying hydroclimatic conditions. During the driest year in the record, almost the entire precipitation was consumed as actual evapotranspiration and only little diffuse recharge took place at the high altitudes of our study site. During wettest year, recharge constituted a much larger fraction of precipitation and occurred at the entire study site. Our new method and our findings are significant for decision makers in similar regions that want to prepare for possible changes of hydroclimatic conditions in the future.
Keywords: Acuíferos; Recursos hidráulicos; Recharge; APLIS method; VarKarst model; Water resources; Karst aquifers